Reflective photomask blank and reflective photomask
By using a multi-layer reflective film and top cover layer in extreme ultraviolet light olithography, combining high absorption coefficient materials and specific metal elements, the projection effect and hydrogen radiation resistance problems are solved, and efficient pattern transfer and long-term stable mask performance are achieved.
Patent Information
- Application Number
- JP2024231803
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
During the extreme ultraviolet light olithography process of light sources in extreme ultraviolet light areas, the projection effect of the reflective mask leads to a degradation of pattern transfer performance, and the existing mask materials are intolerant to hydrogen radiation, affecting the stability of long-term use.
The reflective mask structure of a multi-layer reflective film and a top cover layer is adopted. The low-reflection part uses high absorption coefficient materials (such as titanium, titanium ingot, tungsten, etc.) as the absorption layer, and metal elements such as thorium, titanium, tungsten, and molybdenum are added to the low-reflection part to improve hydrogen radiation tolerance.
It effectively reduces the projection effect, improves the pattern transfer performance, and significantly improves the durability and stability of the photomask in extreme ultraviolet light environments.
Smart Images

Figure 2025038245000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a reflective photomask for use in lithography using light in the ultraviolet region as a light source, and a reflective photomask blank for producing the same. [Background technology]
[0002] In the manufacturing process of semiconductor devices, the demand for miniaturization of photolithography technology is increasing along with the miniaturization of semiconductor devices. The minimum resolution dimension of the transfer pattern in photolithography depends heavily on the wavelength of the exposure light source, and the shorter the wavelength, the smaller the minimum resolution dimension can be. For this reason, the exposure light source is being replaced from the conventional ArF excimer laser light with a wavelength of 193 nm to light in the EUV (Extreme Ultra Violet) region with a wavelength of 13.5 nm.
[0003] Light in the EUV region is absorbed at a high rate by most substances, so a reflective photomask is used as a photomask for EUV exposure (EUV mask) (see, for example, Patent Document 1). Patent Document 1 discloses an EUV photomask obtained by forming a reflective layer made of a multilayer film in which molybdenum (Mo) layers and silicon (Si) layers are alternately laminated on a glass substrate, forming an absorbing layer mainly composed of tantalum (Ta) thereon, and forming a pattern on this absorbing layer.
[0004] Furthermore, as mentioned above, EUV lithography cannot use refractive optics that utilize the transmission of light, so the optical components of the exposure machine are reflective (mirrors) rather than lenses. This creates a problem in that the incident light and reflected light on the reflective photomask (EUV mask) cannot be designed to be coaxial, so EUV lithography normally employs a method in which the optical axis is tilted 6 degrees from the vertical direction of the EUV mask, and the reflected light reflected at an angle of minus 6 degrees is guided to the semiconductor substrate.
[0005] As such, in EUV lithography, the optical axis is tilted via a mirror, which is known to cause a problem known as the "projection effect," in which the EUV light incident on the EUV mask casts a shadow on the mask pattern (patterned absorbing layer) of the EUV mask.
[0006] Current EUV mask blanks use a tantalum (Ta)-based film with a thickness of 60 nm to 90 nm as the absorption layer. When performing pattern transfer exposure with an EUV mask fabricated using this mask blank, there is a risk of a decrease in contrast at the shadow edge of the mask pattern depending on the relationship between the incident direction of the EUV light and the orientation of the mask pattern. This can lead to problems such as increased line edge roughness of the transferred pattern on the semiconductor substrate and inability to form the line width to the targeted dimension, resulting in a deterioration of transfer performance.
[0007] Therefore, reflective photomask blanks are being considered in which the absorption layer is changed from tantalum (Ta) to a material with high absorption (extinction coefficient) for EUV light, or a material with high absorption is added to tantalum (Ta).For example, Patent Document 2 describes a reflective photomask blank in which the absorption layer is made of a material containing 50 atomic % (at %) or more of tantalum (Ta) as the main component, and further containing at least one element selected from tellurium (Te), antimony (Sb), platinum (Pt), iodine (I), bismuth (Bi), iridium (Ir), osmium (Os), tungsten (W), rhenium (Re), tin (Sn), indium (In), polonium (Po), iron (Fe), gold (Au), mercury (Hg), gallium (Ga), and aluminum (Al).
[0008] Furthermore, it is known that mirrors become contaminated by by-products of EUV generation (e.g., tin (Sn)) and carbon (C). Accumulation of contaminants on the mirror can reduce the reflectivity of the mirror surface, lowering the throughput of the lithography apparatus. In response to this problem, Patent Document 3 discloses a method of generating hydrogen radicals within the apparatus, reacting the hydrogen radicals with the contaminants, and removing the contaminants from the mirror.
[0009] However, there is no mention of resistance to hydrogen radicals in the reflective photomask blank described in Patent Document 2. Therefore, the transfer pattern (mask pattern) formed on the absorber layer by introduction into an EUV exposure tool cannot be stably maintained, and as a result, there is a possibility that transferability may deteriorate. [Prior art documents] [Patent documents]
[0010] [Patent Document 1] JP 2011-176162 A [Patent Document 2] JP 2007-273678 A [Patent Document 3] JP 2011-530823 A Summary of the Invention [Problem to be solved by the invention]
[0011] Therefore, an object of the present invention is to provide a reflective photomask blank and a reflective photomask that suppress or reduce the projection effect of a reflective photomask for patterning transfer using light with a wavelength in the extreme ultraviolet region as a light source and have hydrogen radical resistance. More specifically, an object of the present invention is to provide a reflective photomask and a reflective photomask blank for producing the same that reduce the possibility of deterioration in transferability by imparting hydrogen radical resistance to a light absorbing layer. [Means for solving the problem]
[0012] In order to solve the above problems, a reflective photomask blank according to one embodiment of the present invention is a reflective photomask blank for producing a reflective photomask for pattern transfer using extreme ultraviolet light as a light source, comprising: a substrate; a reflective portion formed on the substrate for reflecting incident light; and a low-reflection portion formed on the reflective portion for absorbing the incident light, the reflective portion comprising a multilayer reflective film and a capping layer, the low-reflection portion comprising a high-extinction coefficient material having an extinction coefficient of greater than 0.041 for EUV light, and a tantalum-containing layer. The low-reflection portion includes tantalum (Ta) and at least one of a group of materials consisting of titanium (Ti), niobium (Nb), tungsten (W), and molybdenum (Mo), and the high extinction coefficient material is contained in an amount of more than 50 at%, the content of the at least one of the group of materials consisting of titanium (Ti), niobium (Nb), tungsten (W), and molybdenum (Mo) in the low-reflection portion is less than or equal to the content of tantalum (Ta), the total film thickness of the low-reflection portion is 45 nm or less, and the OD value (Optical Density) of the low-reflection portion is 1.0 or more.
[0013] In order to solve the above problems, a reflective photomask according to one aspect of the present invention is a reflective photomask for pattern transfer using extreme ultraviolet light as a light source, comprising: a substrate; a reflective portion formed on the substrate for reflecting incident light; and a low reflective portion formed on the reflective portion for absorbing the incident light, the reflective portion comprising a multilayer reflective film and a capping layer, the low reflective portion comprising a high extinction coefficient material having an extinction coefficient of greater than 0.041 with respect to EUV light, and at least one selected from a group of materials consisting of tantalum (Ta), titanium (Ti), niobium (Nb), tungsten (W), and molybdenum (Mo), the high extinction coefficient material being greater than 50 at %, and the titanium (Ti), niobium (Nb) and molybdenum (Mo) in the low reflective portion being greater than 50 at %. The content of at least one of a material group consisting of Nb, tungsten (W), and molybdenum (Mo) is less than or equal to the content of tantalum (Ta), the total film thickness of the low-reflection portion is 45 nm or less, and the OD value (Optical Density) of the low-reflection portion is 1.0 or more. Effect of the Invention
[0014] According to one aspect of the present invention, in patterning using light having a wavelength in the extreme ultraviolet region as a light source, the transfer performance to a semiconductor substrate is improved, and resistance to the external environment during the manufacture and use of the photomask can be expected. In other words, the reflective photomask blank and the reflective photomask according to one aspect of the present invention suppress or reduce the projection effect of a reflective photomask for patterning transfer using light having a wavelength in the extreme ultraviolet region as a light source, and have hydrogen radical resistance. [Brief description of the drawings]
[0015] [Figure 1] 1 is a schematic cross-sectional view showing a structure of a reflective photomask blank according to an embodiment of the present invention. [Diagram 2] 1 is a schematic cross-sectional view showing a structure of a reflective photomask according to an embodiment of the present invention. [Diagram 3] 1 is a map showing the refractive index n and the extinction coefficient k at the wavelength of EUV light. [Figure 4] FIG. 11 is a schematic cross-sectional view showing a structure of a reflective photomask according to a modified example of the embodiment of the present invention. [Diagram 5] FIG. 1 is a schematic cross-sectional view showing a structure of a reflective photomask blank according to an embodiment of the present invention. [Figure 6] 1A to 1C are schematic cross-sectional views showing a manufacturing process of a reflective photomask according to an embodiment of the present invention. [Figure 7] 1A to 1C are schematic cross-sectional views showing a manufacturing process of a reflective photomask according to an embodiment of the present invention. [Figure 8] 1A to 1C are schematic cross-sectional views showing a manufacturing process of a reflective photomask according to an embodiment of the present invention. [Figure 9]1 is a schematic cross-sectional view showing a structure of a reflective photomask according to an embodiment of the present invention. [Figure 10] 1 is a schematic plan view showing the shape of a design pattern of a reflective photomask according to an embodiment of the present invention. [Figure 11] FIG. 2 is a schematic cross-sectional view showing a structure of a reflective photomask blank according to a comparative example of the present invention. [Figure 12] FIG. 1 is a schematic cross-sectional view showing a structure of a reflective photomask according to a comparative example of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] Hereinafter, embodiments of the present invention will be described with reference to the drawings, but the present invention is not limited to the embodiments shown below. In the embodiments shown below, technically preferable limitations are imposed for carrying out the present invention, but these limitations are not essential requirements for the present invention. Fig. 1 is a schematic cross-sectional view showing the structure of a reflective photomask blank 10 according to an embodiment of the present invention. Also, Fig. 2 is a schematic cross-sectional view showing the structure of a reflective photomask 20 according to an embodiment of the present invention. Here, the reflective photomask 20 according to the embodiment of the present invention shown in Fig. 2 is formed by patterning the low reflection portion 4 of the reflective photomask blank 10 according to the embodiment of the present invention shown in Fig. 1.
[0017] (Overall structure) As shown in FIG. 1, a reflective photomask blank 10 according to an embodiment of the present invention includes a substrate 1, a multilayer reflective film 2 formed on the substrate 1, and a capping film formed on the multilayer reflective film 2. As a result, a reflective portion 5 having the multilayer reflective film 2 and the capping layer 3 is formed on the substrate 1, and a low-reflection portion 4 is provided on the reflective portion 5.
[0018] (substrate) The substrate 1 according to the embodiment of the present invention may be, for example, a flat silicon (Si) substrate, a synthetic quartz substrate, etc. The substrate 1 may be made of low thermal expansion glass containing titanium (Ti), but the present invention is not limited to these materials as long as they have a small thermal expansion coefficient.
[0019] (Multilayer reflective film) The multilayer reflective film 2 according to the embodiment of the present invention may be any film that reflects EUV light (extreme ultraviolet light) as exposure light, and may be a multilayer reflective film made of a combination of materials that have significantly different refractive indices for EUV light. The multilayer reflective film 2 may be formed by repeatedly stacking layers of a combination of molybdenum (Mo) and silicon (Si), or molybdenum (Mo) and beryllium (Be), for example, for about 40 periods.
[0020] (capping layer) The capping layer 3 according to the embodiment of the present invention is made of a material that is resistant to dry etching performed when forming a transfer pattern (mask pattern) in the low reflection portion 4, and functions as an etching stopper that prevents damage to the multilayer reflective film 2 when etching the low reflection portion 4. The capping layer 3 is made of, for example, Ru (ruthenium). Here, depending on the material of the multilayer reflective film 2 and the etching conditions, the capping layer 3 may not be formed. Although not shown, a back conductive film can be formed on the surface of the substrate 1 on which the multilayer reflective film 2 is not formed. The back conductive film is a film for fixing the reflective photomask 20 by utilizing the principle of an electrostatic chuck when the reflective photomask 20 is placed in an exposure machine.
[0021] (Low reflective part) As shown in FIG. 2, a low-reflection portion pattern 4a of a reflective photomask 20 is formed by removing a part of the low-reflection portion 4 of a reflective photomask blank 10, that is, by patterning the low-reflection portion 4. In EUV lithography, EUV light is incident at an angle and reflected by the reflection portion 5, but the low-reflection portion pattern 4a obstructs the light path, resulting in a projection effect, which may deteriorate the transfer performance onto a wafer (semiconductor substrate). This deterioration in transfer performance can be reduced by reducing the thickness of the low-reflection portion 4 that absorbs EUV light. In order to reduce the thickness of the low-reflection portion 4, it is preferable to use a material that is more absorbent for EUV light than conventional materials, that is, a material with a high extinction coefficient k at a wavelength of 13.5 nm.
[0022] Figure 3 is a graph showing the optical constants of some metal materials for EUV light with a wavelength of 13.5 nm. The horizontal axis of Figure 3 represents the refractive index n, and the vertical axis represents the extinction coefficient k. The extinction coefficient k of tantalum (Ta), which is the main material of the conventional low-reflectivity portion 4, is 0.041. If a material has a larger extinction coefficient k, it is possible to make the low-reflectivity portion 4 thinner than before. Materials that satisfy the above-mentioned extinction coefficient k include, for example, silver (Ag), platinum (Pt), indium (In), cobalt (Co), tin (Sn), nickel (Ni), and tellurium (Te), as shown in FIG.
[0023] The intensity of reflected light from the reflective portion 5 is Rm, and the intensity of reflected light from the low-reflective portion 4 is Ra. The optical density (OD) value, which is an index representing the contrast in light intensity between the reflective portion 5 and the low-reflective portion 4, is defined by the following formula (1). OD = -log(Ra / Rm) Equation (1) The larger the OD value, the better the contrast and the higher the transferability. An OD>1 is necessary, but based on the above comparison with the conventional art, an OD value of 1.5 or more is more preferable.
[0024] As described above, compound materials mainly composed of Ta have been used for the low reflection portion 4 of conventional EUV reflective photomasks. In this case, to obtain an OD value of 1 or more, the film thickness of the low reflection portion 4 needs to be 40 nm or more, and to obtain an OD value of 2 or more, the film thickness of the low reflection portion 4 needs to be 70 nm or more. The extinction coefficient k of tantalum (Ta) is 0.041, and when a material with an extinction coefficient k larger than 0.041 is used as the main component, the low reflection portion 4 can be made thinner than when tantalum (Ta) is used as the main component. In particular, oxides of tin (Sn) and indium (In) are desirable candidate materials for the low reflection portion 4 because they can be etched with chlorine-based gas.
[0025] For example, by applying a material containing tin (Sn) and oxygen (O) with an extinction coefficient k of 0.06 or more, or a material containing indium (In) and oxygen (O) to the low-reflective portion 4, it is possible to reduce the film thickness of the low-reflective portion 4 to 17 nm if the OD value is at least 1, and to reduce the film thickness of the low-reflective portion 4 to 45 nm or less if the OD value is 2 or more. However, if the film thickness of the low-reflective portion 4 exceeds 45 nm, the projection effect will be about the same as that of a low-reflective portion 4 with a film thickness of 60 nm that is formed from a conventional compound material mainly composed of Ta.
[0026] Therefore, the low-reflection portion 4 in the embodiment of the present invention is characterized in that it contains more than 50 at % of a material with an extinction coefficient k greater than 0.041 (hereinafter also referred to as a high extinction coefficient material) and has a film thickness of 45 nm or less. In other words, when the film thickness of the low-reflection portion 4 is within the range of 45 nm or less, the projection effect can be sufficiently reduced and the transfer performance is improved compared to the conventional low-reflection portion 4 formed of a compound material mainly composed of tantalum (Ta). In addition, the content of the above-mentioned high extinction coefficient material is preferably 55 at % or more, and more preferably 60 at % or more, relative to the number of atoms in the entire low-reflection portion 4. Moreover, the above-mentioned “main component” refers to a component that is contained in the low reflection portion 4 at 50 at % or more of the total number of atoms.
[0027] Furthermore, in order to transfer a fine pattern, it is desirable to have a high contrast between the intensity of light reflected from the reflective portion 5 and the low reflective portion 4. Therefore, it is more preferable that the OD value of the low reflective portion 4 is 1.5 or more. Among the high extinction coefficient materials, a material containing tin (Sn) and oxygen (O) or a material containing indium (In) and oxygen (O) has the characteristics of being excellent in etching processability with chlorine-based gases and having a high melting point, resulting in high heat resistance due to exposure to light. Furthermore, among high extinction coefficient materials, materials containing tin (Sn) and oxygen (O) are characterized by excellent cleaning resistance.
[0028] Furthermore, since the reflective photomask 20 is exposed to a hydrogen radical environment, unless the material constituting the low reflection portion 4 is a light absorbing material with high hydrogen radical resistance, the reflective photomask 20 cannot withstand long-term use. In this embodiment, a material or layer formed from a material with a film reduction rate of 0.1 nm / s or less in a hydrogen radical environment with a power of 1 kW and a hydrogen pressure of 0.36 millibars (mbar) or less using microwave plasma is considered to be a material or layer with high hydrogen radical resistance.
[0029] However, among high extinction coefficient materials, there are materials that have low resistance to hydrogen radicals. For example, when only tin oxide is used as the material constituting the low-reflection portion 4, or when a material in which the atomic ratio of tin (Sn) to oxygen (O) is 1:2 or less (i.e., the atomic ratio (O / Sn) of tin (Sn) to oxygen (O) is less than 0.5) is used, it has been confirmed that the hydrogen radical resistance is not good. The atomic ratio is the result of measuring a material formed into a film having a thickness of 1 μm by EDX (energy dispersive X-ray analysis).
[0030] Here, a material containing tantalum (Ta), which will be described later, and at least one of a group of materials consisting of titanium (Ti), niobium (Nb), tungsten (W), and molybdenum (Mo) (hereinafter also referred to as additive alloy materials) satisfies the conditions as a material that enhances the hydrogen radical resistance of the low-reflection portion 4.
[0031] Tantalum (Ta) is a material that contributes to improving hydrogen radical resistance, and materials containing the above-mentioned additive alloy materials are materials that, when combined with tantalum (Ta), increase the mechanical strength of the entire material and contribute to improving the stability of the compound. Here, if the content of tantalum (Ta) is 10 at% or more relative to the total number of atoms in the low reflection portion 4, and the content of the added alloy material is 2.5 at% or more relative to the number of tantalum (Ta) atoms, the film reduction rate of the low reflection portion 4 in the above-mentioned hydrogen radical resistance test is 0.1 nm / s or less. This confirmed that the material of the above composition is a material with high hydrogen radical resistance.
[0032] The above-mentioned tantalum (Ta) content is preferably 15 at% or more, and more preferably 20 at% or more, relative to the total number of atoms in the low reflectivity portion 4. The tantalum (Ta) content is preferably less than 50 at% relative to the total number of atoms in the low reflectivity portion 4, since the effect of the transferability of the high extinction coefficient material is greater. The tantalum (Ta) content is more preferably less than 40 at% relative to the total number of atoms in the low reflectivity portion 4, since the effect of the transferability of the high extinction coefficient material is even greater, and even more preferably less than 35 at%.
[0033] The content of the additive alloy material is preferably 2.5 at% or more relative to the number of tantalum (Ta) atoms, since excellent hydrogen radical resistance can be imparted, and more preferably 5.0 at% or more. The content of the additive alloy material is preferably 15 at% or less relative to the number of tantalum (Ta) atoms, and more preferably 10 at% or less, since the effect on the optical constant of the low reflectivity portion 4 is minimal.
[0034] As described above, the low-reflective portion 4 of the present embodiment contains a high-extinction coefficient material having an extinction coefficient for EUV light greater than 0.041, and an additive alloy material including at least one of the group of materials consisting of tantalum (Ta) and titanium (Ti), niobium (Nb), tungsten (W), and molybdenum (Mo), and contains more than 50 at% of the high-extinction coefficient material with respect to the total number of atoms constituting the low-reflective portion 4, the content of the additive alloy material in the low-reflective portion 4 is equal to or less than the content of tantalum (Ta), the total film thickness of the low-reflective portion 4 is 45 nm or less, and the OD value of the low-reflective portion 4 is 1.0 or more.
[0035] With this configuration, it is possible to provide a reflective photomask 20 with reduced deterioration in transferability by imparting excellent hydrogen radical resistance to the low-reflectivity portion 4 and improving the durability of the low-reflectivity portion 4, and a reflective photomask blank 10 for producing the same. Moreover, the content of the additive alloy material in the low reflection portion 4 is preferably 2.5 at % or more, and more preferably 5 at % or more, relative to the total number of tantalum (Ta) atoms. In addition, the content of titanium (Ti), niobium (Nb), tungsten (W), or molybdenum (Mo) in the low-reflection portion 4 may be 2.5 at % or more with respect to the total number of tantalum (Ta) atoms, and may be less than the content of tantalum (Ta) in the low-reflection portion 4.
[0036] The material constituting the low reflection portion 4 is, for example, beryllium (Be), calcium (Ca), scandium (Sc), vanadium (V), manganese (Mn), iron (Fe), copper (Cu), germanium (Ge), arsenic (As), strontium (Sr), technetium ( By including elements such as ZnO (Tc), rhodium (Rh), barium (Ba), tungsten (W), rhenium (Re), osmium (Os), and gold (Au), the roughness, in-plane dimensional uniformity, and in-plane uniformity of the transferred image can be improved, resulting in a material that is sufficiently amorphous.
[0037] Furthermore, the material constituting the low-reflection portion 4 may contain, for example, chromium (Cr), titanium (Ti), aluminum (Al), silicon (Si), zirconium (Zr), vanadium (V), hafnium (Hf), niobium (Nb), yttrium (Y), lead (Pb), gallium (Ga), etc., so that the material is less likely to react with hydrogen radicals and has higher hydrogen radical resistance. The content of each of the above-mentioned materials is preferably within a range of 1 at% to 10 at% with respect to the total number of atoms in the low-reflection portion 4, and more preferably within a range of 2 at% to 5 at%.
[0038] Furthermore, the material constituting the low reflection portion 4 may contain, for example, tantalum (Ta), niobium (Nb), chromium (Cr), titanium (Ti), aluminum (Al), vanadium (V), hafnium (Hf), etc., so that an oxide film 6 having hydrogen radical resistance can be formed so as to cover the exposed surface of the low reflection portion 4, as shown in Fig. 4. The content of each of the above-mentioned materials is preferably within a range of 1 at% to 10 at% with respect to the number of atoms in the entire low reflection portion 4, and more preferably within a range of 2 at% to 5 at%.
[0039] In addition, the material constituting the low-reflection portion 4 may contain, for example, rhodium (Rh), niobium (Nb), platinum (Pt), titanium (Ti), palladium (Pd), etc., so that the material has low reactivity with chemicals such as SPM and APM that are generally used for mask cleaning, and can be made more resistant to cleaning. Furthermore, the material constituting the low-reflection portion 4 contains, for example, silicon nitride (SiN), tantalum oxide (TaO), or the like, and can be a material that has high light absorption at wavelengths of 190 nm to 260 nm and improves the contrast of the inspection light.
[0040] In addition, the material constituting the low-reflection portion 4 can contain, for example, cobalt (Co), ruthenium (Ru), iridium (Ir), gold (Au), palladium (Pd), platinum (Pt), molybdenum (Mo), etc., and can be a material that has a refractive index n of less than 0.95 for a wavelength of 13.5 nm and improves phase shifting properties. Although examples of the effects of the materials that can be contained in the low-reflectivity portion 4 have been described above, the effects of each material are not limited to the above examples, and each material may have a plurality of effects.
[0041] Furthermore, since the reflective photomask 20 is exposed to a hydrogen radical environment as described above, it cannot withstand long-term use unless the material constituting the low reflection portion 4 is highly resistant to hydrogen radicals. In this embodiment, hydrogen plasma is generated using microwave plasma with a power of 1 kW in a vacuum of 0.36 millibars (mbar) or less, and a material with a film reduction rate of 0.1 nm / s or less in a hydrogen radical-rich environment is defined as a material with high hydrogen radical resistance.
[0042] In addition, in the "hydrogen radical resistance" shown in Table 1 (results of the film reduction rate evaluation test), the film reduction rate was measured multiple times, and a case in which the film reduction rate was 0.1 nm / s or less in all of the measurements was evaluated as "○", a case in which there was a film reduction of several nm immediately after the start of the hydrogen radical treatment but the film reduction rate thereafter was 0.1 nm / s or less was evaluated as "△", and a case in which the film reduction rate exceeded 0.1 nm / s in all of the measurements was evaluated as "×".
[0043] Examples of the reflective photomask blank and the reflective photomask according to the present invention will be described below. [Example 1] 5, a multilayer reflective film 12 is formed by stacking 40 layers of a laminate film made of a pair of silicon (Si) and molybdenum (Mo) on a synthetic quartz substrate 11 having low thermal expansion characteristics. The thickness of the multilayer reflective film 12 is 280 nm. Next, a capping layer 13 made of ruthenium (Ru) was formed as an intermediate film to a thickness of 2.5 nm on the multilayer reflective film 12. As a result, a reflective portion 16 having the multilayer reflective film 12 and the capping layer 13 was formed on the substrate 11.
[0044] Next, the low reflection portion 14 was formed on the capping layer 13 with a homogeneous material of silver oxide (high extinction coefficient material), tantalum, and tungsten (additive alloy material) in a ratio of 54:45:1, to a thickness of 35 nm. The composition ratio at this time was calculated based on the analysis results by Rutherford backscattering spectrometry (RBS). In addition, the crystallinity of the low reflection portion 14 was measured by XRD (X-ray diffraction device), and it was found to be amorphous. As a result, the low reflection portion 14 was formed on the reflection portion 16.
[0045] Next, a back conductive film 15 made of chromium nitride was formed to a thickness of 100 nm on the surface of the substrate 11 on which the multilayer reflective film 12 was not formed, thereby producing the reflective photomask blank 100 of Example 1. A multi-target sputtering device was used to deposit each film on the substrate 11. The thickness of each film was controlled by the sputtering time.
[0046] Next, a method for producing the reflective photomask 200 will be described with reference to FIGS. As shown in FIG. 6, a positive chemically amplified resist (SEBP9012: manufactured by Shin-Etsu Chemical Co., Ltd.) was spin-coated to a thickness of 120 nm on the low-reflection portion 14 of the reflective photomask blank 100, and baked at 110° C. for 10 minutes to form a resist film 17. Next, a predetermined pattern was drawn on the resist film 17 formed of a positive chemically amplified resist by an electron beam lithography machine (JBX3030: manufactured by JEOL Ltd.). After that, a baking process was performed at 110° C. for 10 minutes, and then a spray development (SFG3000: manufactured by Sigma Meltec Co., Ltd.) was performed. As a result, a resist pattern 17a was formed as shown in FIG. 7.
[0047] Next, the low reflection portion 14 was patterned by dry etching mainly using a chlorine-based gas to form a low reflection portion pattern 14a as shown in FIG. Next, the remaining resist pattern 17a was peeled off to produce a reflective photomask 200 according to this embodiment as shown in FIG. Next, the reflective photomask 200 according to this embodiment was immersed in sulfuric acid at 80°C for 10 minutes, and then immersed in a cleaning tank filled with a cleaning solution of ammonia, hydrogen peroxide, and water in a ratio of 1:1:20 for 10 minutes using 500W megasonics, and washed with running water for 10 minutes. After that, the film thickness was measured with an AFM (atomic force microscope) and compared with the film thickness at the time of film formation, but no change was observed in the film thickness. From this result, it can be seen that the reflective photomask 200 according to this embodiment has excellent cleaning resistance.
[0048] In this embodiment, the low reflection portion pattern 14a formed in the low reflection portion 14 includes a 64 nm line-and-space (LS) pattern, a 200 nm line-width LS pattern for measuring the film thickness of the low reflection portion 14 using an AFM, and a 4 mm square low reflection portion removed portion for measuring the EUV reflectance on a reflective photomask 200 for transfer evaluation. The 64 nm line-width LS pattern was designed in each of the x and y directions as shown in FIG. 10 so that the influence of the projection effect caused by oblique irradiation of EUV can be easily seen.
[0049] [Example 2] The low reflection portion 14 is made of silver oxide (high extinction coefficient material) and tantalum and tungsten (additive alloy material). The material was homogeneous with a ratio of 53.9:44:2.1, and the film was formed to a thickness of 35 nm. The composition ratio at this time was calculated based on the analysis results by Rutherford backscattering spectrometry (RBS). Furthermore, the crystallinity of the low reflection portion 14 was measured by XRD (X-ray diffraction device), and it was found to be amorphous. As a result, the low reflection portion 14 was formed on the reflection portion 16. The reflective photomask blank 100 and the reflective photomask 200 of Example 2 were produced in the same manner as in Example 1, except for the low reflection portion 14.
[0050] [Example 3] The low reflection portion 14 was formed to a thickness of 35 nm using a homogeneous material of tin oxide (high extinction coefficient material), tantalum, and tungsten (additive alloy material) in a ratio of 53.9:44:2.1. The composition ratio was calculated based on the analysis results of Rutherford backscattering spectrometry (RBS). The crystallinity of the low reflection portion 14 was measured by XRD (X-ray diffraction device) and found to be amorphous. As a result, the low reflection portion 14 was formed on the reflection portion 16. The reflective photomask blank 100 and the reflective photomask 200 of Example 3 were produced in the same manner as in Example 1 except for the low reflection portion 14.
[0051] [Example 4] The low reflection portion 14 was formed to a thickness of 26 nm using a homogeneous material of silver oxide (high extinction coefficient material), tantalum, and tungsten (additive alloy material) in a ratio of 78:20:2. The composition ratio was calculated based on the analysis results of Rutherford backscattering spectrometry (RBS). The crystallinity of the low reflection portion 14 was measured by XRD (X-ray diffraction device) and found to be amorphous. As a result, the low reflection portion 14 was formed on the reflection portion 16. The reflective photomask blank 100 and the reflective photomask 200 of Example 4 were produced in the same manner as in Example 1 except for the low reflection portion 14.
[0052] [Example 5] The low reflection portion 14 was formed to a thickness of 26 nm using a homogeneous material of tin oxide (high extinction coefficient material), tantalum, and tungsten (additive alloy material) in a ratio of 78:20:2. The composition ratio was calculated based on the analysis results of Rutherford backscattering spectrometry (RBS). The crystallinity of the low reflection portion 14 was measured by XRD (X-ray diffraction device) and found to be amorphous. As a result, the low reflection portion 14 was formed on the reflection portion 16. The reflective photomask blank 100 and the reflective photomask 200 of Example 5 were produced in the same manner as in Example 1 except for the low reflection portion 14.
[0053] [Example 6] The low reflection portion 14 was formed to a thickness of 26 nm using a homogeneous material of indium oxide (high extinction coefficient material), tantalum, and tungsten (additive alloy material) in a ratio of 78:20:2. The composition ratio was calculated based on the analysis results of Rutherford backscattering spectrometry (RBS). The crystallinity of the low reflection portion 14 was measured by XRD (X-ray diffraction device) and found to be amorphous. As a result, the low reflection portion 14 was formed on the reflection portion 16. The reflective photomask blank 100 and the reflective photomask 200 of Example 6 were produced in the same manner as in Example 1 except for the low reflection portion 14.
[0054] [Example 7] The low reflection portion 14 was formed to a thickness of 26 nm using a homogeneous material of tin oxide (high extinction coefficient material), tantalum, and titanium (additive alloy material) in a ratio of 78:20:2. The composition ratio was calculated based on the analysis results of Rutherford backscattering spectrometry (RBS). The crystallinity of the low reflection portion 14 was measured by XRD (X-ray diffraction device) and found to be amorphous. As a result, the low reflection portion 14 was formed on the reflection portion 16. The reflective photomask blank 100 and the reflective photomask 200 of Example 7 were produced in the same manner as in Example 1 except for the low reflection portion 14.
[0055] [Example 8] The low reflection portion 14 was formed to a thickness of 26 nm using a homogeneous material of tin oxide (high extinction coefficient material), tantalum, and niobium (additive alloy material) in a ratio of 78:20:2. The composition ratio was calculated based on the analysis results of Rutherford backscattering spectrometry (RBS). The crystallinity of the low reflection portion 14 was measured by XRD (X-ray diffraction device) and found to be amorphous. As a result, the low reflection portion 14 was formed on the reflection portion 16. The reflective photomask blank 100 and the reflective photomask 200 of Example 8 were produced in the same manner as in Example 1 except for the low reflection portion 14.
[0056] [Example 9] The low reflection portion 14 was formed to a thickness of 26 nm using a homogeneous material of tin oxide (high extinction coefficient material), tantalum, and molybdenum (additive alloy material) in a ratio of 78:20:2. The composition ratio was calculated based on the analysis results of Rutherford backscattering spectrometry (RBS). The crystallinity of the low reflection portion 14 was measured by XRD (X-ray diffraction device) and found to be amorphous. As a result, the low reflection portion 14 was formed on the reflection portion 16. The reflective photomask blank 100 and the reflective photomask 200 of Example 9 were produced in the same manner as in Example 1 except for the low reflection portion 14.
[0057] [Comparative Example 1] The low reflection portion 14 was formed to a thickness of 35 nm using a homogeneous material of silver oxide (high extinction coefficient material) and tantalum in a ratio of 55:45. The composition ratio was calculated based on the analysis results by Rutherford backscattering spectrometry (RBS). The crystallinity of the low reflection portion 14 was measured by XRD (X-ray diffraction) and found to be amorphous. As a result, the low reflection portion 14 was formed on the reflection portion 16. The reflective photomask blank 100 and the reflective photomask 200 of Comparative Example 1 were produced in the same manner as in Example 1 except for the low reflection portion 14.
[0058] [Comparative Example 2] As shown in Fig. 11, the absorbing layer 241 was formed of tantalum nitride and was deposited to a thickness of 58 nm. The outermost layer 242 was formed of tantalum oxide and was deposited to a thickness of 2 nm. As a result, a low-reflecting portion 24 having the absorbing layer 241 and the outermost layer 242 was formed on the reflective portion 16. This comparative example was based on a conventional reflective photomask made of an existing film mainly composed of tantalum. However, the tantalum nitride and tantalum oxide are separated into an upper layer and a lower layer, and the film does not have a continuously changing composition. A reflective photomask blank 101 and a reflective photomask 201 having a low-reflection pattern 24a of Comparative Example 2 shown in Figures 11 and 12 were produced in the same manner as in Example 1, except for the formation of the absorption layer 241 and the outermost layer 242.
[0059] The reflectance Rm of the reflective region and the reflectance Ra of the low-reflectance region of the reflective photomask produced in the above-mentioned Examples and Comparative Examples were measured using a reflectance measuring device using EUV light. The reflectance Rm was measured at a 4 mm square low-reflectance removed portion. From the measurement results, the OD value was calculated using the above-mentioned formula (1).
[0060] (Wafer exposure evaluation) Using an EUV exposure tool (NXE3300B: manufactured by ASML), the low reflection pattern 14a, 24a of the reflective photomask prepared in the examples and comparative examples was transferred onto a semiconductor wafer coated with an EUV positive chemically amplified resist. At this time, the exposure dose was x The LS pattern in the direction was adjusted so as to be transferred as designed. After that, the transferred resist pattern was observed and the line width was measured by an electron beam dimension measuring device to confirm the resolution. In this case, the HV-bias was rated as "△" for the existing film with a thickness of 6.1 nm, "○" for less than 6.1 nm, and "◎" for 4.5 nm or less, while the OD value was rated as "○" for 1.5 or more, and "◎" for 1.7 or more. For HV-bias, if the evaluation was "△" or higher, there were no problems with use, so it was considered to have passed. For OD value, if the evaluation was "○" or higher, there were no problems with use, so it was considered to have passed. The evaluation results are shown in Table 1.
[0061] [Table 1]
[0062] Table 1 shows the resist pattern dimensions on the wafer and the mask characteristics of a photomask in a Ta-based existing film in Comparative Example 2, in which the absorption layer 241 is made of tantalum nitride and has a thickness of 58 nm, and the outermost layer 242 is made of tantalum oxide and has a thickness of 2 nm. In the case of the reflective photomask 201 in Comparative Example 2, the film reduction rate in the hydrogen radical resistance evaluation was 0.1 nm / s or less. The OD value was 1.5, and the contrast was such that the pattern could be transferred. As a result of patterning using EUV light, the HV bias (horizontal-vertical dimension difference) was 6.1 nm, and although the image was resolved, the shadowing effect was large, resulting in low transferability.
[0063] The reflective photomask 201 of Comparative Example 2 was immersed in sulfuric acid at 80°C for 10 minutes, then immersed in a cleaning tank filled with a cleaning solution of ammonia, hydrogen peroxide, and water in a ratio of 1:1:20 for 10 minutes using 500W megasonics, and washed with running water for 10 minutes. The thickness was then compared with that at the time of film formation, but no change was observed in the thickness. From this result, it was found that the reflective photomask 201 of Comparative Example 2 has excellent cleaning resistance.
[0064] In Table 1, in Example 1, the resist pattern dimensions on the wafer and the mask characteristics are shown for a photomask in which the low reflection portion 14 is made of a homogeneous material of silver oxide (high extinction coefficient), tantalum, and tungsten (additive alloy material) in a ratio of 54:45:1, and the film thickness is 35 nm. In the case of the reflective photomask 200 of Example 1, a film loss of 1 nm was observed immediately after the start of the hydrogen radical treatment, but no film loss was observed thereafter. The OD value was 2.5, and a contrast capable of pattern transfer was obtained. As a result of patterning using EUV light, the HV bias was 5.7 nm, and superior pattern transferability was obtained compared to Comparative Example 2.
[0065] The reflective photomask 200 of Example 1 was immersed in sulfuric acid at 80°C for 10 minutes, then immersed in a cleaning tank filled with a cleaning solution of ammonia, hydrogen peroxide, and water in a ratio of 1:1:20 for 10 minutes using 500W megasonics, and washed with running water for 10 minutes. The thickness was compared with the thickness at the time of film formation, but no change was observed. From this result, it was found that the reflective photomask 200 of Example 1 has excellent cleaning resistance.
[0066] In Table 1, in Example 2, the low reflection portion 14 is made of a homogeneous material in which silver oxide (high extinction coefficient material), tantalum, and tungsten (additive alloy material) are mixed in a ratio of 53.9:44:2.1. The figure shows the resist pattern dimensions on the wafer and the mask characteristics for a photomask having a film thickness of 35 nm. For the reflective photomask 200 of Example 2, no film loss was observed in the hydrogen radical resistance evaluation, and excellent hydrogen radical resistance was obtained. The OD value was 2.4, and a contrast capable of pattern transfer was obtained. As a result of patterning using EUV light, the HV bias was 5.6 nm, and excellent pattern transferability was obtained compared to Comparative Example 2.
[0067] The reflective photomask 200 of Example 2 was immersed in sulfuric acid at 80°C for 10 minutes, then immersed in a cleaning tank filled with a cleaning solution of ammonia, hydrogen peroxide, and water in a ratio of 1:1:20 for 10 minutes using 500W megasonics, and washed with running water for 10 minutes. The thickness was compared with the thickness at the time of film formation, but no change was observed. From this result, it was found that the reflective photomask 200 of Example 2 has excellent cleaning resistance.
[0068] In Table 1, in Example 3, the resist pattern dimensions on the wafer and the mask characteristics are shown for a photomask in which the low reflection portion 14 is made of a homogeneous material of tin oxide (high extinction coefficient material), tantalum, and tungsten (additive alloy material) in a ratio of 53.9:44:2.1, and the film thickness is 35 nm. With the reflective photomask 200 of Example 3, no film loss was observed in the hydrogen radical resistance evaluation, and excellent hydrogen radical resistance was obtained. The OD value was 1.7, and a contrast capable of pattern transfer was obtained. As a result of patterning using EUV light, the HV bias was 4.6 nm, and excellent pattern transferability was obtained compared to Comparative Example 2.
[0069] The reflective photomask 200 of Example 3 was immersed in sulfuric acid at 80° C. for 10 minutes, and then washed in a cleaning tank filled with a cleaning solution of ammonia, hydrogen peroxide, and water in a ratio of 1:1:20. The film thickness was compared with that at the time of film formation, but no change was observed. From this result, it was found that the reflective photomask 200 of Example 3 has excellent cleaning resistance.
[0070] In Table 1, in Example 4, the resist pattern dimensions on the wafer and the mask characteristics are shown for a photomask in which the low reflection portion 14 is made of a homogeneous material of silver oxide (high extinction coefficient material), tantalum, and tungsten (additive alloy material) in a ratio of 78:20:2, and the film thickness is 26 nm. With the reflective photomask 200 of Example 4, no film loss was observed in the hydrogen radical resistance evaluation, and excellent hydrogen radical resistance was obtained. The OD value was 1.6, and a contrast capable of pattern transfer was obtained. As a result of patterning using EUV light, the HV bias was 3.8 nm, and excellent pattern transferability was obtained compared to Comparative Example 2.
[0071] The reflective photomask 200 of Example 4 was immersed in sulfuric acid at 80°C for 10 minutes, then immersed in a cleaning tank filled with a cleaning solution of ammonia, hydrogen peroxide, and water in a ratio of 1:1:20 for 10 minutes using 500W megasonics, and washed with running water for 10 minutes. The film thickness was compared with that at the time of film formation, but no change was observed. From this result, it was found that the reflective photomask 200 of Example 4 has excellent cleaning resistance.
[0072] In Table 1, in Example 5, the resist pattern dimensions on the wafer and the mask characteristics are shown for a photomask in which the low reflection portion 14 is made of a homogeneous material of tin oxide (high extinction coefficient material), tantalum, and tungsten (additive alloy material) in a ratio of 78:20:2, and the film thickness is 26 nm. With the reflective photomask 200 of Example 5, no film loss was observed in the hydrogen radical resistance evaluation, and excellent hydrogen radical resistance was obtained. The OD value was 1.7, and a contrast capable of pattern transfer was obtained. As a result of patterning using EUV light, the HV bias was 3.0 nm, and excellent pattern transferability was obtained compared to Comparative Example 2.
[0073] The reflective photomask 200 of Example 5 was immersed in sulfuric acid at 80°C for 10 minutes, then immersed in a cleaning tank filled with a cleaning solution of ammonia, hydrogen peroxide, and water in a ratio of 1:1:20 for 10 minutes using 500W megasonics, and washed with running water for 10 minutes. The thickness was compared with that at the time of film formation, but no change was observed in the thickness. From this result, it was found that the reflective photomask 200 of Example 5 has excellent cleaning resistance.
[0074] In Table 1, in Example 6, the resist pattern dimensions on the wafer and the mask characteristics are shown for a photomask in which the low reflection portion 14 is made of a homogeneous material of indium oxide (high extinction coefficient material), tantalum, and tungsten (additive alloy material) in a ratio of 78:20:2, and the film thickness is 26 nm. With the reflective photomask 200 of Example 6, no film loss was observed in the hydrogen radical resistance evaluation, and excellent hydrogen radical resistance was obtained. The OD value was 1.7, and a contrast capable of pattern transfer was obtained. As a result of patterning using EUV light, the HV bias was 3.0 nm, and excellent pattern transferability was obtained compared to Comparative Example 2.
[0075] The reflective photomask 200 of Example 6 was immersed in sulfuric acid at 80°C for 10 minutes, then immersed in a cleaning tank filled with a cleaning solution of ammonia, hydrogen peroxide, and water in a ratio of 1:1:20 for 10 minutes using 500W megasonics, and washed with running water for 10 minutes. The thickness was compared with that at the time of film formation, but no change was observed in the thickness. From this result, it was found that the reflective photomask 200 of Example 6 has excellent cleaning resistance.
[0076] In Table 1, in Example 7, the low reflection portion 14 is made of a material in which tin oxide (high extinction coefficient material), tantalum, and titanium (additive alloy material) are homogeneously mixed in a ratio of 78:20:2, and the resist pattern dimensions on the wafer and the mask characteristics of the photomask having a film thickness of 26 nm are In the case of the reflective photomask 200 of Example 7, no film loss was observed in the hydrogen radical resistance evaluation, and excellent hydrogen radical resistance was obtained. The OD value was 1.7, and a contrast capable of pattern transfer was obtained. As a result of patterning using EUV light, the HV bias was 3.0 nm, and excellent pattern transferability was obtained compared to Comparative Example 2.
[0077] The reflective photomask 200 of Example 7 was immersed in sulfuric acid at 80°C for 10 minutes, then immersed in a cleaning tank filled with a cleaning solution of ammonia, hydrogen peroxide, and water in a ratio of 1:1:20 for 10 minutes using 500W megasonics, and washed with running water for 10 minutes. The film thickness was compared with that at the time of film formation, but no change was observed. From this result, it was found that the reflective photomask 200 of Example 7 has excellent cleaning resistance.
[0078] In Table 1, in Example 8, the resist pattern dimensions on the wafer and the mask characteristics are shown for a photomask in which the low reflection portion 14 is made of a homogeneous material of tin oxide (high extinction coefficient material), tantalum, and niobium (additive alloy material) in a ratio of 78:20:2, and the film thickness is 26 nm. With the reflective photomask 200 of Example 8, no film loss was observed in the hydrogen radical resistance evaluation, and excellent hydrogen radical resistance was obtained. The OD value was 1.7, and a contrast capable of pattern transfer was obtained. As a result of patterning using EUV light, the HV bias was 3.0 nm, and excellent pattern transferability was obtained compared to Comparative Example 2.
[0079] The reflective photomask 200 of Example 8 was immersed in sulfuric acid at 80°C for 10 minutes, then immersed in a cleaning tank filled with a cleaning solution of ammonia, hydrogen peroxide, and water in a ratio of 1:1:20 for 10 minutes using 500W megasonics, and washed with running water for 10 minutes. The thickness was compared with that at the time of film formation, but no change was observed in the thickness. From this result, it was found that the reflective photomask 200 of Example 8 has excellent cleaning resistance.
[0080] In Table 1, in Example 9, the resist pattern dimensions on the wafer and the mask characteristics are shown for a photomask in which the low reflection portion 14 is made of a homogeneous material of tin oxide (high extinction coefficient material), tantalum, and molybdenum (additive alloy material) in a ratio of 78:20:2, and the film thickness is 26 nm. With the reflective photomask 200 of Example 9, no film loss was observed in the hydrogen radical resistance evaluation, and excellent hydrogen radical resistance was obtained. The OD value was 1.7, and a contrast capable of pattern transfer was obtained. As a result of patterning using EUV light, the HV bias was 3.0 nm, and excellent pattern transferability was obtained compared to Comparative Example 2.
[0081] The reflective photomask 200 of Example 9 was immersed in sulfuric acid at 80° C. for 10 minutes, then immersed in a cleaning tank filled with a cleaning solution of ammonia, hydrogen peroxide, and water in a ratio of 1:1:20 for 10 minutes using 500 W megasonics, and washed with running water for 10 minutes. The film thickness was compared with that at the time of film formation, but no change was observed. From this result, it was found that the reflective photomask 200 of Example 9 has excellent cleaning resistance.
[0082] In Table 1, in Comparative Example 1, the resist pattern dimensions on the wafer and the mask characteristics are shown for a photomask in which the low reflection portion 14 is made of a homogeneous material of silver oxide (high extinction coefficient material) and tantalum in a ratio of 55:45, and the film thickness is 35 nm. For the reflective photomask 200 of Comparative Example 1, the film reduction rate in the hydrogen radical resistance evaluation was 0.11 nm / s. The OD value was 1.7, and a contrast capable of pattern transfer was obtained. As a result of patterning using EUV light, the HV bias was 3.0 nm, and superior pattern transferability was obtained compared to Comparative Example 2.
[0083] The reflective photomask 200 of Comparative Example 1 was immersed in sulfuric acid at 80° C. for 10 minutes, then immersed in a cleaning tank filled with a cleaning solution of ammonia, hydrogen peroxide, and water in a ratio of 1:1:20, using 500 W megasonics for 10 minutes, and washed with running water for 10 minutes. The film thickness was compared with the thickness at the time of film formation, but no change was observed in the film thickness. From this result, it was found that the reflective photomask 200 of Comparative Example 1 has excellent cleaning resistance.
[0084] Comparing Example 1 with the existing film (Comparative Example 2), it was found that the hydrogen radical resistance of the reflective photomask of Example 1 was slightly inferior to that of the reflective photomask using the existing film, but the pattern transferability of the reflective photomask of Example 1 was superior to that of the reflective photomask using the existing film. Note that, since the reflective photomask of Example 1 was slightly inferior to that of the existing film in hydrogen radical resistance and superior in pattern transferability, the judgment result was marked as "△" and treated as "passed."
[0085] Comparing Examples 2 to 9 with the existing film (Comparative Example 2), it was found that the hydrogen radical resistance of each of the reflective photomasks of Examples 2 to 9 was equivalent to that of the reflective photomask using the existing film, and the pattern transferability of each of the reflective photomasks of Examples 2 to 9 was superior to that of the reflective photomask using the existing film. Note that, since each of the reflective photomasks of Examples 2 to 9 was superior to that of the existing film (Comparative Example 4) in both hydrogen radical resistance and pattern transferability, the judgment result was marked as "◯" and treated as "passed." The reflective photomask of Comparative Example 1 was clearly inferior in hydrogen radical resistance to that of the existing film (Comparative Example 2), and was therefore judged as "X" and treated as a "failure."
[0086] As a result, the reflective photomask 200 in which the low-reflection portion 14 contains more than 50 at% of a high-extinction coefficient material, which is a material having an extinction coefficient for EUV light greater than 0.041, and contains tantalum (Ta) and at least one of a group of materials consisting of titanium (Ti), niobium (Nb), tungsten (W) and molybdenum (Mo), and the content (content of the added alloy material) is less than or equal to the content of tantalum (Ta) contained in the low-reflection portion 14, the film thickness is 45 nm or less, and the OD value is 1.0 or more, has good pattern transferability and hydrogen radical resistance, can reduce the projection effect, has a long life, and has high transfer performance. In other words, it was confirmed that a reflective photomask 200 with better transfer performance can be obtained. In other words, it has been confirmed that by using the reflective photomask blank 100 according to the above embodiment, it is possible to suppress or reduce the projection effect of a reflective photomask for patterning transfer using light with a wavelength in the extreme ultraviolet region as a light source, and to fabricate a reflective photomask 200 having excellent hydrogen radical resistance. [Industrial Applicability]
[0087] The reflective photomask blank and reflective photomask according to the present invention can be suitably used for forming fine patterns by EUV exposure in the manufacturing process of semiconductor integrated circuits and the like. [Explanation of symbols]
[0088] 1. Circuit board 2...Multilayer reflective film 3. Capping layer 4...Low reflective area 4a Low reflection pattern 5...Reflector 6. Oxide film 6a Oxide film pattern 10. Reflective photomask blank 20. Reflective photomask 11... Circuit board 12...Multilayer reflective film 13. Capping layer 14...Low reflective area 14a Low reflection pattern 24...Low reflective area 241...Absorption layer 242...uppermost layer 24a Low reflection pattern 15 Back conductive film 16...Reflector 17. Resist film 17a Resist pattern 100···Reflective Photomask Blank 200···Reflective photomask 101 Reflective photomask blank 201 Reflective photomask
Claims
1. A reflective photomask blank for producing a reflective photomask for pattern transfer using extreme ultraviolet light as a light source, comprising: A substrate; A reflecting portion formed on the substrate for reflecting incident light; a low-reflection portion formed on the reflection portion and absorbing incident light, the reflective portion includes a multilayer reflective film and a capping layer; the low reflectivity portion includes a high extinction coefficient material having an extinction coefficient of greater than 0.041 for EUV light, and at least one selected from a group of materials consisting of tantalum (Ta), titanium (Ti), niobium (Nb), tungsten (W), and molybdenum (Mo), and the high extinction coefficient material is contained in an amount of greater than 50 at %, a content of at least one of the materials consisting of titanium (Ti), niobium (Nb), tungsten (W), and molybdenum (Mo) in the low-reflection portion is equal to or lower than a content of tantalum (Ta); The total film thickness of the low reflection portion is 45 nm or less, A reflective photomask blank, wherein the low reflection portion has an OD (Optical Density) value of 1.0 or more.
2. 2. The reflective photomask blank according to claim 1, characterized in that the content of at least one of the group of materials consisting of titanium (Ti), niobium (Nb), tungsten (W), and molybdenum (Mo) in the low-reflection portion is 2.5 at % or more with respect to the total number of tantalum (Ta) atoms.
3. 2. The reflective photomask blank according to claim 1, characterized in that the content of at least one of the group of materials consisting of titanium (Ti), niobium (Nb), tungsten (W), and molybdenum (Mo) in the low-reflection portion is 5 at % or more with respect to the total number of atoms of tantalum (Ta).
4. 2. The reflective photomask blank according to claim 1, characterized in that the content of the titanium (Ti), niobium (Nb), tungsten (W), or molybdenum (Mo) in the low-reflection portion is 2.5 at % or more with respect to the total number of atoms of the tantalum (Ta) and is equal to or less than the content of the tantalum (Ta).
5. 5. The reflective photomask blank according to claim 2, wherein the low-reflection portion contains, as the high extinction coefficient material, at least one of a material containing tin (Sn) and oxygen (O) and a material containing indium (In) and oxygen (O).
6. A reflective photomask for pattern transfer using extreme ultraviolet light as a light source, A substrate; A reflecting portion formed on the substrate for reflecting incident light; a low-reflection portion formed on the reflection portion and absorbing incident light, the reflective portion includes a multilayer reflective film and a capping layer; the low reflectivity portion includes a high extinction coefficient material having an extinction coefficient of greater than 0.041 for EUV light, and at least one selected from a group of materials consisting of tantalum (Ta), titanium (Ti), niobium (Nb), tungsten (W), and molybdenum (Mo), and the high extinction coefficient material is contained in an amount of greater than 50 at %, a content of at least one of the materials consisting of titanium (Ti), niobium (Nb), tungsten (W), and molybdenum (Mo) in the low-reflection portion is equal to or lower than a content of tantalum (Ta); The total film thickness of the low reflection portion is 45 nm or less, The reflective photomask is characterized in that the low reflection portion has an OD (Optical Density) value of 1.0 or more.
7. 7. The reflective photomask according to claim 6, wherein the content of at least one of the materials consisting of titanium (Ti), niobium (Nb), tungsten (W), and molybdenum (Mo) in the low-reflection portion is 2.5 at % or more with respect to the total number of tantalum (Ta) atoms.
8. 7. The reflective photomask according to claim 6, wherein the content of at least one of the materials consisting of titanium (Ti), niobium (Nb), tungsten (W), and molybdenum (Mo) in the low-reflection portion is 5 at % or more with respect to the total number of atoms of tantalum (Ta).
9. 7. The reflective photomask according to claim 6, wherein the content of titanium (Ti), niobium (Nb), tungsten (W), or molybdenum (Mo) in the low-reflection portion is 2.5 at % or more with respect to the total number of atoms of tantalum (Ta) and is equal to or less than the content of tantalum (Ta).
10. 10. The reflective photomask according to claim 7, wherein the low-reflection portion contains at least one of a material containing tin (Sn) and oxygen (O) and a material containing indium (In) and oxygen (O) as the high extinction coefficient material.
Citation Information
Patent Citations
Reflection type photomask blank, reflection type photomask, and method of manufacturing semiconductor device
JP2010103463A
Masks for EUV lithography, EUV lithography systems, and methods for optimizing mask imaging.
JP2013532381A
Reflective photomask blank and reflective photomask
JP2019139085A
Reflection type mask blank, reflection type mask and method for manufacturing semiconductor device
JP2020106639A
Reflective photomask blank and reflective photomask
JP2020197606A